TREATMENT QUALITY OF PATIENTS WITH ARTERIAL HYPERTENSION IN THE OUTPATIENT SETTING - O. V. Poltoratskaya (Российский кардиологический журнал, 2003)
Prevalence of modifying risk factors and quality of its correction were studied in 150 patients with arterial hypertension II-III stage. Study revealed poor blood pressure control, high prevalence of risk factor and insufficient quality of its correction. The most frequent risk factor was dislipidemia in 41,3 % of patients. There were no patients with control of dislipidemia by statins.